Kharisma Kyai Dalam Organisasi Pendidikan Pesantren Tradisional - Umi Musaropah (Universitas Cokroaminoto Yogyakarta, 2018)
Islamic boarding schools (pesantren) are very complex because of the variety of education held. Therefore, the role of the clerics as a charismatic leader in them is needed so that education can be sustainable. Qualitative research at pesantren At-Tanwir in Bojonegoro Regency uses data collection instruments in the form of; observation, in-depth interviews and documentation. For data validation, it was determined through an extension of the research time and the results crossing based on the research tool category